Synthesis and characterisation of MIL-101(Cr) using different additives / Effah Yahya … [et al.] - Yahya, Effah; Mohd Samsul Anuar, Nur Alia; Ismail, Ahmad Fauzi; Nik Ab Lah, Nik Khairul Irfan; Mat Yusuf, Suriatie; Che Abdul Rahim, Azzah Nazihah (Universiti Teknologi MARA Shah Alam, 2023)
MIL-101(Cr), a subgroup of metal-organic framework that has the capabilities as an adsorbent for CO2 removal because of its large pore volume and high surface area. It is now commonly used to remove CO2 from raw natural gas components as well as capture or lower CO2 from flue gas or the atmosphere. The presence of CO2 in raw natural gas will corrode the pipelines and lower the heating value which will lead to an increase in transportation costs. Therefore, it is significant to study the synthesis of MIL-101(Cr) with improved properties. Generally, the morphology and properties improvement of MIL-101(Cr) can be modified by the addition of additives or modulators (i.e., NaOH, HNO3, HF). Hence, the objectives of this study are to synthesise the metal-organic framework of MIL-101(Cr) with different additives, and to characterise and analyse the synthesised MIL-101(Cr). The effect of adding modulators (additives) to MIL-101(Cr) was systematically discussed through X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), and Fourier Transform Infrared Spectroscopy (FTIR) analysis. The results showed that the Cr component was successfully integrated into each sample and MIL-101(Cr) – Non has a small particle size which indicates a larger surface area thus reflecting high porosity. It also has unsaturated metal sites which makes it excellent properties for gas adsorption.